2010
DOI: 10.17221/18/2009-pps
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and aggressiveness of Fusarium oxysporum Schl. in bottle gourd and bitter gourd

Abstract: Cumagun C.J.R., Aguirre J.A., Relevante C.A., Balatero C.H. (2010): Pathogenicity and aggressiveness of Fusarium oxysporum Schl. in bottle gourd and bitter gourd. Plant Protect. Sci., 46: 51-58.Fusarium oxysporum is responsible for a large range of diseases on economically important crops such as bitter gourd and bottle gourd. Pathogenicity and aggressiveness of F. oxysporum in bitter gourd and bottle gourd isolated from two breeding stations of East-West Company in the Philippines namely San Ildefonso, Bulaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
6
1
1
Order By: Relevance
“…This finding deviated from the previous reports that the FOM isolates could infect the seedling and adult plants of white flower L. siceraria (Zhu and Qi ; Cumagun et al. ). The pathogenicity variation in L. siceraria might be attributed to different variants of L. siceraria .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding deviated from the previous reports that the FOM isolates could infect the seedling and adult plants of white flower L. siceraria (Zhu and Qi ; Cumagun et al. ). The pathogenicity variation in L. siceraria might be attributed to different variants of L. siceraria .…”
Section: Discussioncontrasting
confidence: 99%
“…Zhu and Qi showed that cross infectivity of FOM from bitter gourd was pathogenic to bottle gourd seedlings and club bottle gourd seedlings and adult plants [7]. Cumagun et al found that some FOM isolates from bitter gourd could infect 7-days-old bottle gourd seedlings, while they could not infect the 1-month-old adult plants [4]. Chen et al also reported that some FOM isolates from bitter gourd slightly infected bottle gourd ( Lagenaria siceraria var.…”
Section: Discussionmentioning
confidence: 99%
“…Bitter gourd ( Momordica charantia L.) wilt caused by Fusarium oxysporum f. sp. momordicae Sun & Huang (FOM), is one of the most disastrous diseases in China [1], Japan [2], India [3] and Philippine [4]. Sun and Huang firstly reported that the occurrence of bitter gourd wilt disease in Taiwan, China[5], which has become prevalent since 1996 [6].…”
Section: Introductionmentioning
confidence: 99%
“…F. solani dapat menyebabkan gejala layu pada Cucurbitaceae yang sering dikacaukan dengan gejala layu yang disebabkan oleh F. oxysporum. Perbedaan keduanya ialah F. solani tidak bersifat sistemik seperti halnya F. oxysporum yang lebih dikenal sebagai penyebab penyakit jaringan pembuluh (Snyder dan Hansen 1941;Cumagun et al 2010). F. solani f.sp.…”
Section: Pembahasanunclassified